PERAN KHUSUS VERBA “MEMASAK” DALAM BAHASA BALI: KAJIAN METABAHASA SEMANTIK ALAMI (MSA) - Ida Bagus Pramana Pidada; I Nengah Sudipa; Ni Made Suryati (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2018)
Observasion of Special Role of Verba”Memasak”” Bali Language (VMBB): Metalanguage Analysis of Natural Semantic analyses semantic aspect, firstly lexical realization and verb classification “memasak” in Bali langage (VMBB) mainly special role of argument semantic VMBB. Determination of the argument roles VMBB using theory of general role (Macroroles) analyses semantic role VMBB. Im general, ACTOR in VMBB acts as agent, UNDERGOER act as patient. Role analyses in this observation are done in layers to determine a semantic in an argument. The analyses of this observation use the design of qualitative observation, meanwhile the collection of data is done by observation method, interview, recording, and noting. Data analysis is done by distributional method by using replacement technique (substitution). The next method is description of special role of verb “memasak” in Bali language (VMBB). Analysis is assisted with explication technique. The presentation of result analysis of the data is done by the method of description, formal, and informal. Lexicon of verba”memasak” in Bali language (VMBB) is found 12 firstly: nyakan,mubuh, ngoreng, ngepes, ngnyahnyah, nadang, nunu, nambus, ngatim, nguskus, nguling, and nglablab.The result of observation shous that the lexion of VMBB have special role firstly as agent and patient.